Impact of Heavy Vehicles on Urban Road Performance Using Indonesian Highway Capacity Guidelines 2023: A Case Study of an Urban Arterial Road in Kendari City Indonesia - Nuhun, Ridwan Syah; Welendo, La; Siolimbona, Indra; Rausy, Endang Pratiwi; Anwar, Muhamad (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2026)
Big trucks totally mess up traffic in cities, specially when mixed in with cars n bikes. This study evaluates the impact of heavy vehicles on Z. A. Sugianto Road, Kendari City, using the updated Indonesian Highway Capacity Guidelines (PKJI 2023). We ran a three-day traffic survey during the busy morning, midday, and evening rushes. It captured things like traffic volumes, mix of vehicles, speeds, and those nagging side frictions. From there, we calculated roadway capacity, degree of saturation (DS), and Level of Service (LOS) under two setups: one with heavy vehicles and one without. The numbers tell a clear story—heavy vehicles make up just 4.2–5.3% of the traffic, but they bump DS up from 0.42 to 0.47 and drop LOS from B to C. Side frictions cut the effective capacity even more, from 6,800 down to 5,461 pcu/h. Overall, the new PKJI 2023 parameters do a better job spotting how heavy vehicles mess with urban mixed traffic. This work gives real-world tips for city traffic managers, like controlling heavy vehicles, tackling side frictions, and checking performance regularly to keep roads safe and running smoothly.